Simple Scoring System to Predict In‐Hospital Mortality After Surgery for Infective Endocarditis. Issue 7 (July 2017) - Gatti, Giuseppe; Perrotti, Andrea; Obadia, Jean‐François; Duval, Xavier; Iung, Bernard; Alla, François; Chirouze, Catherine; Selton‐Suty, Christine; Hoen, Bruno; Sinagra, Gianfranco; Delahaye, François; Tattevin, Pierre; et al.
Abstract : Background: Aspecific scoring systems are used to predict the risk of death postsurgery in patients with infective endocarditis (IE). The purpose of the present study was both to analyze the risk factors for in‐hospital death, which complicates surgery for IE, and to create a mortality risk score based on the results of this analysis. Methods and Results: Outcomes of 361 consecutive patients (mean age, 59.1±15.4 years) who had undergone surgery for IE in 8 European centers of cardiac surgery were recorded prospectively, and a risk factor analysis (multivariable logistic regression) for in‐hospital death was performed. The discriminatory power of a new predictive scoring system was assessed with the receiver operating characteristic curve analysis. Score validation procedures were carried out. Fifty‐six (15.5%) patients died postsurgery. BMI >27 kg/m 2 (odds ratio [OR], 1.79; P =0.049), estimated glomerular filtration rate <50 mL/min (OR, 3.52; P <0.0001), New York Heart Association class IV (OR, 2.11; P =0.024), systolic pulmonary artery pressure >55 mm Hg (OR, 1.78; P =0.032), and critical state (OR, 2.37; P =0.017) were independent predictors of in‐hospital death. A scoring system was devised to predict in‐hospital death postsurgery for IE (area under the receiver operating characteristic curve, 0.780; 95% CI, 0.734–0.822). The score performed better than 5 of 6 scoring systems for in‐hospital death after cardiac surgery that were considered. Conclusions: A simple scoring system based on risk factors for in‐hospital death was specifically created to predict mortality risk postsurgery in patients with IE.